2014
DOI: 10.5176/2345-7872_1.2.15
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence and Optimistic Cognitive Style in Certainty in Career Decision Making

Abstract: Abstract-The current study tested whether Trait Emotional Intelligence variables and Optimistic Cognitive Style together predicted feelings of certainty in career decision making. Few studies have examined the effects of trait emotional intelligence or life style orientation on career choice, and no study has been found that combined both the life orientation (optimism) and the trait emotional intelligence domains and facets: this current study examined the relative weights of these facets and lifestyle orient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…Our findings support the hypothesis that the negative view of the future in victims of IPV is attributable to their difficulties understanding, managing, and using their own emotions (Hypotheses 1). It is likely that high levels of trait EI reduce pessimistic future views and increase optimistic ones ( Alexander et al., 2014 ; Farnia et al., 2018 ). It is also plausible that high levels of trait EI may help female victims of IPV escape abusive situations.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings support the hypothesis that the negative view of the future in victims of IPV is attributable to their difficulties understanding, managing, and using their own emotions (Hypotheses 1). It is likely that high levels of trait EI reduce pessimistic future views and increase optimistic ones ( Alexander et al., 2014 ; Farnia et al., 2018 ). It is also plausible that high levels of trait EI may help female victims of IPV escape abusive situations.…”
Section: Discussionmentioning
confidence: 99%
“…Petrone (2000) reported that more developed vocational identity as compared to females and have more optimistic approach regarding the future success of their career. Optimistic cognitive style is more positively and significantly related to career certanity among university students (Alexander, et al, 2014).…”
Section: Figurementioning
confidence: 92%
“…Previous research support this notion that gender difference is prevalent in career decision making difficulties of students at various levels, therefore the aim of the present research is explore the gender difference in career decision difficulties of college students. Cognitive style is influential in decision making, it was corelated with various career related variable i.e., internal and external career barriers, career choice etc (Creed, et al, 2004;Alexander, et al, 2014), but gender differnce was not observed specifically. So the present study will explore the gender difference in cognitive styles of college students.…”
Section: Figurementioning
confidence: 96%
See 1 more Smart Citation
“…Selain kepribadian, berdasarkan penelitian-penelitian sebelumnya optimisme juga sering dikaitkan dengan beberapa hal seperti kecerdasan emosional, sosial ekonomi, parental supporti, depresi, self efficacy, dan self mastery. Alexander et al (2014) menyebutkan bahwa optimisme secara signifikan berkaitan dengan kecerdasan emosional seseorang. Sementara Carver et al (2010) menjelaskan bahwa status sosial ekonomi orangtua seperti pendidikan, jenis pekerjaan, dan jabatan orangtua juga memiliki hubungan positif terhadap tingkat optimisme anak pada saat mereka dewasa.…”
Section: Pendahuluanunclassified